Delineating Functional Regions and Application in Health Geography - Liu, Lingbo; Wang, Fahui (Computational Methods and GIS Applications in Social Science - Lab Manual, 2024)
A functional region is an area around a node, facility, or hub connected by a certain function (e.g., retail distribution, health care service, advertisement for a media company, or telecom coverage). By defining a functional region, a distinctive market area has a geographic boundary that encompasses many smaller areas more closely connected than beyond. Defining functional regions is a classic task in geography. It can be as straightforward as the proximal area method that assigns areas to their nearest facility, or the Huff model that accounts for the joint effects of facility sizes and their distances from residents. Unlike these two popular methods, two other approaches, the Refined Dartmouth Method and Spatialized Network Community Detection Methods, utilize observed service flows between areas to define functional regions, here hospital service areas (HSAs) in the case studies.